Nilai Kemanusiaan pada Novel Sepatu Terakhir Karya Toni Tegar Sahidi - Diana, Ani (JURNAL PESONA, 2017)
AbstractThis study aims to describe the values of humanity in the novel Shoes Last Toni Tegar Sahidi. The method used in this research is a descriptive method. The novels are analyzed and interpreted based on existing theory, then described in accordance with the objectives of the study. From the results of data analysis, there are eight human values, namely: human and love, human and beauty, human and suffering, human and justice, human and responsibility, human and life view, human and anxiety, and human and hope.Keywords: literature, novel, human value.